CHARITIES AND TAXATION: MAIN TRENDS IN COMPARATIVE PERSPECTIVE AT THE BEGINNING OF THE 21ST CENTURY - A. S. Avtonomov; V. V. Grib (Sravnitelʹnai͡a︡ politika (Moscow, Russia), 2020)
Taxation in the modern society has become to play role of one of important and efficient instruments of the State in carrying out its social and economic policy. Eminent French scholar Maurice Duverger wrote shortly after the middle of the 20th century in his famous book “Public Finances” that the tax “ceases to be the grain of sand that interferes with the gears in order to become one of the regulators and engines of the machine. The tax levies on prices and incomes do not only aim to cover the expenses of the State apparatus, but to ensure a certain correction and a certain orientation of the mechanisms of the market. The “interventionist” goal is thus added to the “financial” goal; the tax becomes an essential instrument of the economic policy of the State, and also of its social policy (action on the income by the taxation). The conclusions made by M. Duverger do not lose their relevance today. There is neither need nor necessity to prove or explain that charitable activity helps the State, where it unfolds, to resolve social problems. By means of taxation States offer incentives to support tendencies consistent with their preferences in social policy and put constraints in order to impede tendencies, which are considered to be undesirable. Of course, with change of a Government preferences and undesirability may shift, however Governments act on behalf of their States. So, a taxation goal to maintain by collective efforts a State, which seemed to be unique in the times of Adam Smith, who wrote that “the necessary expence of any great and civilized state… must, the greater part of it, be defrayed by taxes of one kind or another” (with his four maxims [principles] “with regard to taxes in general” – equity understanding as proportionality [“the subjects of every state ought to contribute towards the support of the government, as nearly as possible, in proportion to their respective abilities”]; certainty as opposing to arbitrary actions [“the time of payment, the manner of payment, the quantity to be paid ought all to be clear and plain to the contributor, and to every other person”]; convenience for the contributor [“the tax is levied at the time when it is most likely to be convenient for the contributor to pay; or, when he is most likely to have wherewithal to pay”]; economical approach [“every tax ought to be contrived as both to take out and to keep out of the pockets of the people as little as possible, over and above what it brings into the public treasury of the state”]), is added by a taxation goal to regulate economic and social State policies. Therefore, it is taken into consideration in the present article that any contemporary State uses taxation as a regulatory tool in the sphere of charitable activity.